Efektifitas Teknik Cognitif Restructuring Pada Pendekatan CBT Untuk Mereduksi Negative Self-Concept - Timothy Vito Pattipeihulu; Maghfirotul Lathifah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
This study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT) using cognitive restructuring techniques in reducing negative self-concept among university students. An experimental method with a Single Subject Research (SSR) design of A-B-A was employed, consisting of Baseline 1 (A), Intervention (B), and Baseline 2 (A) phases. The participant was a 22-year-old fifth-semester university student who experienced a high level of negative self-concept due to complex psychosocial experiences. Data were collected using a Likert-scale self-concept questionnaire and self-observation records assessing independence, self-esteem, emotional regulation, and self-confidence. The results indicated that the participant obtained a pre-test score of 54, reflecting a high level of negative self-concept. During the initial baseline phase, self-observation scores fluctuated and tended to decline. Following ten sessions of CBT using cognitive restructuring techniques, the post-test score increased to 69, indicating a reduction in negative self-concept. In the second baseline phase, self-observation scores remained stable, demonstrating that the therapeutic gains were maintained over time. These findings indicate that Cognitive Behavioral Therapy with cognitive restructuring techniques is effective in reducing negative self-concept among university students.